EBV-driven diffuse large B-cell lymphoma confined to the liver in a patient with a history of idiopathic CD4 lymphocytopenia. (21st August 2013) - Dziadzio, Magdalena; Chee, Ronnie; McNamara, Christopher; Deheragoda, Maesha; Wagner, Thomas; Seneviratne, Suranjith L
Abstract : Idiopathic CD4 lymphocytopenia (ICL) is a rare immunodeficiency disorder. We describe a 49-year-old woman with a history of ICL who developed hepatic Epstein-Barr virus (EBV)-positive diffuse large B-cell lymphoma (DLBCL). ICL was diagnosed at a time of her presentation with varicella-zoster virus (VZV) meningoencephalitis and chorioretinitis. Her CD4 count subsequently improved but remained at the lower limits of the normal range. Five years later she presented with cough, fever and night-sweat. She was found to have multiple liver nodules on MRI, fluorodeoxyglucose (FDG) avid on the positron emission tomography (PET) CT, histologically defined as DLBCL, EBV positive and of non-germinal centre type. To our knowledge this is the first reported case of EBV-positive DLBCL localised to the liver in the context of ICL. EBV-positive DLBCL typically occurs in immunocompromised individuals. The corticosteroid therapy she received for VZV meningoencephalitis may have contributed to the EBV reactivation with subsequent EBV-driven malignant transformation of B-cells.